"# FITNESS": impact of Instagram on exercise adherence and self-efficacy. Issue 2 (4th March 2022) - Chaudhary, Kritika; Dhillon, Megha
ABSTRACT: This experimental study aimed to examine the impact of Instagram on adherence to an exercise regimen and self-efficacy to exercise, among Indian female college students. The study was conducted as a two-week intervention. The sample ( n  = 102 for week 1; 68 for week 2) consisted of unmarried, female undergraduate students in the age range of 18–22 years (mean age = 19.03 years). Participants in the experimental and control conditions were provided the same weekly exercise plans. Additionally, the experimental group was exposed to Instagram posts related to exercise. All the participants were requested to fill out adherence sheets at the end of each week, assessing whether they had followed the prescribed exercise schedules. Self-efficacy to exercise was measured before and immediately after the intervention. Participants' perceptions of the entire experience were assessed through an on-line survey conducted at the end of two weeks. Data were analysed using z -test of proportions, t -test for independent samples and content analysis (for the survey). Results indicated that there were no significant differences in adherence rates for both groups in week 1 or week 2 (week 1: z  = 1.01, p  = 0.156; week 2: z  = 1.31, p  = .095). However, the experimental group showed a significantly higher self-efficacy to exercise than the control group, after the intervention ( t  = 1.79, p  = .03). Survey results suggested specific barriers to exercise across both groups with lack of time emerging as the most common barrier. Further, participants in the experimental group desired the use of more attractive and frequently posted Instagram features.